Trace metal distributions in the transition zone from the Greenland Ice Sheet to the surface water in Kangerlussuaq fjord (67° N) - C. R. Vives; J. Bendtsen; R. D. Dahms; N. Daugbjerg; K. V. Larsen; M. T. Rosing (The Cryosphere)
Glacial rock flour (GRF), an ultra-fine sediment formed beneath glaciers, contains high concentrations of silicate and trace metals, including iron (Fe) and manganese (Mn). In Greenland, meltwater discharge transports approximately 1.28 Gt of suspended sediments annually into the oceans, significantly influencing trace metal concentrations and marine biogeochemical cycles. This study investigates the spatial distribution of trace metals, nutrients, and suspended sediment concentration (SSC) from the Russell Glacier at the Greenland Ice Sheet, through the Akuliarusiarsuup Kuua meltwater and into the Kangerlussuaq fjord in western Greenland. Dissolved trace metals were relatively high in the river with low-salinity surface waters in the fjord, showing that the fjord acts as an important source of trace metals for the marine environment. However, trace metal concentrations, particularly Fe and zinc (Zn), exhibited significant non-linear decreases beyond salinity levels of 14, underscoring the complex processes affecting trace metal supply from rivers to fjords and coastal waters. In contrast, silicate concentrations increased in river water due to weathering of GRF and decreased gradually in the inner fjord due to mixing with surface water. Uranium (U) and molybdenum (Mo) were undetectable along the river but increased in the fjord, indicating that these elements primarily originate from the ocean. These findings highlight the complex interplay of physical, chemical, and biological processes regulating trace metal and nutrient dynamics in glacier-influenced fjord systems, with implications for primary productivity and carbon cycling in polar oceans.